PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE (GCG) DAN KINERJA KEUANGAN TERHADAP KUALITAS PENGUNGKAPAN SUSTAINABILITY REPORT (Studi Pada BUMN yang Terdaftar di BEI 2021-2022) - Siti Widya Ningsih; Cut Sukmawati (Program Studi Administrasi Bisnis, 2023)
This research aims to analyze the influence of Good Corporate Governance and Financial Performance on the quality of Sustainability Report disclosures in State-Owned Enterprises (BUMN) companies listed on the Indonesia Stock Exchange (BEI) in the 2021-2022 period. Data was obtained from the official website of the Indonesian Stock Exchange (www.idx.co.id) and the official website of each company. The research sample was 23 companies. This research uses a quantitative approach. The data analysis method used in this research is the Multiple Linear Regression method and the samples selected used the purposive sampling method, namely a sampling technique with certain criteria. Analysis of research data processing using Microsoft Office Excel 2021 and SPSS 25.0 for Windows software. The research results show that the Board of Commissioners and the Board of Directors have a significant positive influence on the closure of sustainability reports, while the audit committee and profitability do not have a significant influence on the closure of sustainability reports.